Implementasi Data Keuangan Menggunakan Zahir Accounting Pada Toko Perabotan Aulia - Meli Zulyanti; Sifa Fauziah (LPPM Universitas Bina Sarana Informatika, 2022)
A financial application is one solution to avoid errors and processing financial data twice for each financial report. Even though it is the digitalization era, there are still business processes that are carried out conventionally, although using a computer it is not optimal because it has not been integrated with the existing system, the process takes a long time and is less accurate. The method used for this research is to use the method of observation, interviews, and literature study. The implementation of Zahir Accounting is expected to simplify the process of recording financial data at the Aulia Furniture store. Aulia Furniture is a trading company that still uses conventional records such as financial reports and transactions, by still using manual recording, it is likely that there will be many errors in calculating and recording financial data, unable to see graphs of financial report developments. If you use the Zahir Accounting application in terms of storing financial data, it will be safer and neater.